State of immunity in pregnant women with undifferentiated connective tissue dysplasia due to cytomegalovirus infection. - Sh. Q. Kadimova (Pediatric Anesthesia and Critical Care Journal, 2024)
To achieve the purpose of the study, based on developed clinical and laboratory criteria, a prospective study of the course of pregnancy and its outcomes was conducted in 62 pregnant women aged 18 to 39 years (average age 27.98±5.3) for the period from 2019 to 2022. with undif- ferentiated connective tissue dysplasia (UCTD), which formed a high-risk group for the development of pathol- ogy of the fetoplacental system. All pregnant women were divided into 2 groups: main (n = 36), comparison (n = 32). The first group of the study (main) consisted of 36 pregnant women with UCTD, carriers of cytomegalovi- rus infection, the second group (comparison) 32 pregnant women with UCTD, without carriage of cytomegalovirus infection. The control group consisted of 24 pregnant women without the presence of UCTD and cytomegalo- virus infection at the time of the study. The conducted studies found that disturbances in the cellular immune system in women with UCTD increased the frequency of the infectious process. In the third trimester, women in the main group were more likely to have threatened labor (15 women (41.7±8.2% in the main group and 6 women (18.8±6.9%) in the comparison group); oligohydramnios (9 women (25 .0±7.2%) and 3 women (9.4±5.1%); intrauterine growth retardation syndrome (28 women (77.8±6.9% and 19 women (59.4±8.6 %). This was re- flected in the high concentration of IgM and an increase in the relative number of CD16+ and CD20+ lympho- cytes in pregnant women of the main group. Histological examination confirmed a higher frequency of infection of the ovum in pregnant women with UCTD, carriers of cy- tomegalovirus, which was limited to the placenta and was not accompanied by intrauterine infection of the fetus. The presence of UCTD in pregnant women with persis- tent infection of the herpesvirus family increases the risk of unfavorable implementation of the infectious process, and this should be taken into account when making a prognosis for the development of obstetric and perinatal complications and justifies the advisability of carrying out treatment and preventive measures during pregnancy and in the postpartum period.